THE SOCIELY OF KNOWLEDGE: URGENT PROBLEMS OF TEACHING POLITICAL SCINCES AT HIGHER SCHOOL - Москальова, Н.П. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
Urgent problems of Ukraine’s higher education development in the context of its integration into united European educational space are considered. The tendencies and prospects of humanization of the higher technical education are analyzed, the importance of the political knowledge for this process is emphasized.